A Novel Non-invasive Biosensor Based on Electric Field Detection for Cardio-electrophysiology in Zebrafish Embryos. (2017) - Rendon-Morales, E.; Prance, R.J.; Prance, H.; Aviles-Espinosa, R.
Abstract: In this paper we report a novel biosensor based on electric field detection for recording cardiac electrical activity in zebrafish embryos. Using Sussex patented Electric Potential Sensing technology, a portable, non-invasive and cost-effective platform is developed to monitor in vivo electrocardiogram activity from the zebrafish heart. Cardiac activity signals were successfully detected from living zebrafish embryos starting at 3 days-post-fertilization. The recorded waveforms contain typical traces such present in electrocardiogram, such as the QRS complex, P and T waves. This research opens new pathways for investigating cardiac related pathologies present at embryonic stages using a novel non-invasive biosensor.